Customer segmentation in retail facility location planning - Sven Müller; Knut Haase (Business Research, 2014)
In this contribution, we discuss a facility location model to maximize firms' patronage, while demand is determined by a multinomial logit model (MNL). We account for customer segmentation based on customer characteristics. Hence, we are able to reduce the bias to the objective, which is due to constant substitution patterns of the MNL. Numerical studies show that averaging customer characteristics yield a bias of more than 15 % of the objective function value compared to segmentation. Using GAMS/CPLEX, we are able to solve problem sets with 2 segments, 500 demand points and 10 potential locations to optimality in 1 h computation time. If we consider 50 potential locations, the gap reported by CPLEX is <8 % in 1 h. We present an illustrative case example of a furniture store company in Germany (data are available as electronic supplementary material to this article). The corresponding problem is solved to optimality in a few minutes.
Keywords: C61; C35; C44; R32; 330; Multinomial logit model; Facility location; Maximum capture problem; Customer choice; Heterogeneous demand; Substitution patterns